Halo Effect as Bobby Nasution and Aulia Rachman's Political Communication Strategy in the 2020 Medan City Local Leader Election - Rania Pramesthi Putri; Anang Sujoko; Desi Prianti (Syntax Corporation Indonesia, 2023)
Bobby Nasution, who is the son-in-law of President Joko Widodo, running for mayor of Medan, North Sumatra, is an interesting topic to discuss. Bobby Nasution was accompanied by Aulia Rachman as Deputy Mayor of Medan, North Sumatra. With the pairing of Bobby Nasution and Aulia Rachman running to become the Mayor and Deputy Mayor of Medan, it attracts public attention, because people often look at the background of a candidate to determine whether the candidate is good or bad. This is known as the halo effect strategy. This study aims to explain the halo effect as a political communication strategy for the pair Bobby Nasution and Aulia Rachman in the 2020 Medan City Election. This study uses a qualitative method with a constructivism paradigm and utilizes data collection techniques in the form of in-depth interviews. The results of this study indicate that the use of the halo effect as a political communication strategy forms a positive political image, this is also in line with the vision and mission of Bobby Nasution and Aulia Rachman, namely the Medan Berkah Collaboration, to form a positive image by bringing what is needed by the people of Medan City.